Utilização de uma Base de Dados em CD-ROM no Centro de Documentação Científica e Técnica do INIC - Silva, Gabriela Lopes (1991)
Utilização de uma Base de Dados em CD-ROM no Centro de Documentação Científica e Técnica do INIC